Learning about What? Non-Confessional Religious Education after the Dissolution of the Binary Categories ‘Religion’ and ‘Secular’ - Peder Thalén (Social Sciences, 2023)
The binary division between ‘religion’ and ‘secular’ as an analytical tool has long been criticised within the research field of ‘critical religion’ in religious studies. There has also been a parallel critique in the academic discussion about post-secularity. Recently, sociologists have picked up and deepened this criticism, as expressed in Mitsutoshi Horii’s book ‘Religion’ and ‘Secular’ Categories in Sociology: Decolonizing the Modern Myth (2021). Based on a critical processing of Horii’s application to sociology, the aim of this article is to discuss the challenges for non-confessional religious education (RE) that the ongoing dismantling of this binary division entails. In particular, it looks at how a non-confessional RE could be designed that transcends the binary division and how powerful knowledge could be understood in a non-binary context.